2019
DOI: 10.1557/jmr.2018.500
|View full text |Cite
|
Sign up to set email alerts
|

Hot deformation behavior of the high-entropy alloy CoCuFeMnNi

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Various deterministic domains and instability regimes have been systematically characterized in this study, whereas other studies limited their characterization to few domains. A safe hot working window has also been identified in the present study based on the outcome of the processing map, corroborated with in-depth microstructural analysis, in comparison to previous works [21][22][23].…”
Section: Conceptual Processing Mapsupporting
confidence: 90%
See 1 more Smart Citation
“…Various deterministic domains and instability regimes have been systematically characterized in this study, whereas other studies limited their characterization to few domains. A safe hot working window has also been identified in the present study based on the outcome of the processing map, corroborated with in-depth microstructural analysis, in comparison to previous works [21][22][23].…”
Section: Conceptual Processing Mapsupporting
confidence: 90%
“…powder metallurgy (P/M) superalloy Nimonic AP-1 [18], Zr-alloys [19], Titanium alloys [20], etc. Besides, few studies have recently appeared in literature illustrating the characterization of hot workability of few HEAs through the development of processing maps, such as CoCrFeMnNi HEA [21] CoCuFeNiMn HEA [22], and CoCuFeNiTi HEA [23] etc. Although, some authors [21][22][23] have reported hot workability of HEAs, none of them conducted an in-depth analysis in terms of microstructural correlation over each domain in the processing map constructed based on the DMM using a wide range of temperatures and strain rates.…”
Section: Introductionmentioning
confidence: 99%
“…High entropy alloys (HEAs) consisting of multi-principal elements are changing the traditional definition of metallurgical alloys and exploring the unknown territories of alloy design [ 1 ]. Recent reports illustrate the excellent mechanical properties of HEAs in many aspects, such as the trade-off between tensile strength and ductility at cryogenic temperatures [ 2 ] and acceptable mechanical endurance in high-temperature environments [ 2 , 3 ]. Several studies attempt to elevate the mechanical performance of novel HEA systems through solid solution strengthening [ 4 , 5 ], precipitation hardening [ 6 , 7 ], and grain refinement strengthening [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the investigation of hot deformation behavior and dynamic recrystallization mechanism is a prerequisite for controlling the grain size and morphology [19][20][21]. The hot compression behaviors of CoCrFeMnNi HEA at various temperatures higher than 800 • C have been studied, and the constitutive equations were formulated for describing the interdependency between deformation temperature, strain rate, flow stress, and strain [22][23][24][25][26]. It was found that the microstructure evolution at the temperatures is accompanied by discontinuous dynamic recrystallization (dDRX), where the dynamic recrystallization (DRX) grains nucleated along initial grain boundaries resulting in the necklace like structures [24][25][26].…”
Section: Introductionmentioning
confidence: 99%